Rare Mineral Evidence of Mahsuri Ring Meteorite Impact in Langkawi Island - Catur Cahyaningsih; Husnul Kausarian; Yogi Aditia (Politeknik Negeri Batam, 2019)
The research area was conducted in Ulu Melaka Village, district of Langkawi, Kedah Province, Malaysia. Coordinate of research area around latitude 99°45'97